Aging, Secular Stagnation and the Business Cycle - Jones, Callum (Washington, D.C. : International Monetary Fund, 2018)
As of 2015, U.S. log output per capita was 12 percent below what its pre-2008 linear trend would predict. To understand why, I develop and estimate a model of the US with demographics, real and monetary shocks, and the occasionally binding ZLB on nominal rates. Demographic changes generate slow-moving trends in the real interest rate, employment, and productivity. I find that demographics alone can explain one-third of the gap between log output per capita and its linear trend in 2015. Demographics also lowered real rates, causing the ZLB to bind between 2009 and 2015, contributing to the slow recovery after the Great Recession.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet